Diseño del sistema de gestión de seguridad y salud en el trabajo para la empresa Agregados y Servicios Fénix Sas (2020)
The main objective of this work was to design an occupational health and safety management system for the company AGREGADOS Y SERVICIOS FÉNIX S.A.S. Decree 1072 of 2015 was used as a guide for the development of the work, in order to minimize or eliminate the risks to which employees are exposed during their working hours in order to improve safety standards. The first thing that was done to fulfill the main purpose of the work was an evaluation of the socio-demographic profile, the objectives and structure of the occupational health and safety management system were established. Immediately, an identification of risks and dangers to which the people who work in the company are exposed, and finally, a management system was designed that meets the requirements and guidelines required in Decree 1072 of 2015, where prepared the necessary documentation for its subsequent implementation